2021
DOI: 10.3390/jcs5050132
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mechanical Properties of Green Insulation Composites Made from Cannabis and Bark Residues

Abstract: The objective of this paper was to investigate the technical feasibility of manufacturing low density insulation particleboards that were made from two renewable resources, namely hemp fibers (Cannabis sativa) and pine tree bark, which were bonded with a non-toxic methyl cellulose glue, as a binder. Four types of panels were made, which consisted of varying mixtures of tree bark and hemp fibers (tree bark to hemp fibers percentages of 90:10, 80:20, 70:30, and 60:40). An additional set of panels was made, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Additionally, they may act as a humidity buffer, reduce moisture, and enhance interior air quality, enabling the structure to "breathe" [25]. Environmental and health impacts of natural materials are similarly negligible, provided they can be bound into thermal insulation boards without the use of chemical adhesives, as in the case of agro-waste [26][27][28] and other unconventional resources [29]. Paper waste and recycled paper are potentially viable alternatives for a sustainable thermal insulation board market [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, they may act as a humidity buffer, reduce moisture, and enhance interior air quality, enabling the structure to "breathe" [25]. Environmental and health impacts of natural materials are similarly negligible, provided they can be bound into thermal insulation boards without the use of chemical adhesives, as in the case of agro-waste [26][27][28] and other unconventional resources [29]. Paper waste and recycled paper are potentially viable alternatives for a sustainable thermal insulation board market [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that the addition of hemp fibres to furnish improved mechanical properties of boards to reach an acceptable level. The thermal conductivity unfavorably increased as hemp content increased, though all values were still within the acceptable range [ 9 ]. Kosinski et al investigated the thermal insulation properties of industrial hemp.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it should be emphasized that only the accumulated volume of wood waste in the world is significant (from 7% to 40% of the wood processing amount per year) [19], and therefore an active search is underway for ways to effectively dispose of it and convert it into a sustainable energy source [20,21]. At the same time efforts have also been undertaken to exploit waste wood by-products towards novel composites, contributing to reduced energy input [22]. The types of biomass that have potential applications in the energy sector vary depending on the region.…”
Section: Introductionmentioning
confidence: 99%